Large specific surface area and rigid network of nanocellulose govern the thermal stability of polymers: Mechanisms of enhanced thermomechanical properties for nanocellulose/PMMA nanocomposite. (September 2018) - Fujisawa, Shuji; Togawa, Eiji; Kimura, Satoshi
Graphical abstract: Abstract: Cellulose nanofibrils (CNFs) are an ideal candidate for green nanofillers in polymer nanocomposites. Benefiting from the unique structural features of CNFs, mechanical and thermal properties of polymers are efficiently improved. To tailor the material properties, we must first understand how the features of CNFs lead to their function. Here, thermomechanical properties of CNF/poly(methylmethacrylate) (PMMA) nanocomposite were investigated through several approaches with a focus on understanding how the nanosize of CNFs influences the properties. Results confirmed that the nanocomposite film showed efficient improvements in thermal dimensional stability and storage modulus by achieving homogeneous and individual dispersion of CNF in the matrix. Moreover, the ultrathin width of the CNF could maintain high optical transparency of PMMA.